Esomeprazole versus omeprazole for the eradication of Helicobacter pylori infection - Ageeli, Rawan; Binobaid, Abdullah; Aljadaan, Abdullah; Alhagbani, Mohammed; Alotaibi, Yasser; Alenazi, Thamer; Alhajjaj, Mohammed; Altawili, Abdullh; Alotaibi, Fuad; Felimban, Najlaa (International Journal Of Community Medicine And Public Health, 2018)
Background: Proton pump inhibitors (PPIs) are one of the most commonly used classes of drugs. Though, the quantum clinical beneﬁt of newer and more expensive PPIs over the older generation PPIs residues undefined. The present meta-analysis ought to assess the safety and clinical proﬁles of esomeprazole versus omeprazole at pharmacologically equivalent doses in healing gastroesophageal reﬂux disease (GERD), peptic ulcer disease and eradicating Helicobacter pylori infection. Methods: PubMed and the Cochrane Library were searched for randomized controlled trials comparing esomeprazole with omeprazole at all doses up to July 2017. Meta-analysis was conducted using a random effects model, and heterogeneity in the estimated effects was investigated using meta-regression. Results: Eleven trials were included and none of which compared esomeprazole with omeprazole in peptic ulcer disease. In gastroesophageal reﬂux disease, esomeprazole 40 mg (relative risk (RR) = 1.11; 95% confidence interval (CI) 1.14 to 1.23) and 20 mg (RR=1.08; 95% CI 1.02 to 1.12) significantly improved esophagitis healing when compared with omeprazole 20 mg at week 8. In H. pylori eradication, there was no difference in the treatment effects between esomeprazole 20 mg and omeprazole 20 mg (RR = 1.05;95% CI 1.01 to 1.11). Conclusions: Esomeprazole established better esophagitis healing rate in patients with GERD than omeprazole at week 8. Though, this clinical advantage reduced when both drugs were given at the same doses at week 4. Superiority of esomeprazole was not perceived in the H. pylori eradication rates.